Global Risk-Based Management of Chemical Additives I Production, Usage and Environmental Occurrence - Bilitewski, Bernd; Darbra, Rosa Mari.; Barcelo, Damia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Chemical additives are used to enhance the properties of many industrial products. Since their release into the environment is a potential risk for man and nature, their fate and behavior were investigated in the framework of the European Union-funded project RISKCYCLE. The results are presented in two volumes, Global Risk-Based Management of Chemical Additives I: Production, Usage and Environmental Occurrence and Global Risk-Based Management of Chemical Additives II: Risk-Based Assessment and Management Strategies. This book is the first of the two volumes and contains two main parts. The chapters of the first part provide a thorough review of the chemical additives used in the textile, plastics, lubricants, paper, leather and electronics industries, and describe the effect of each additive on the properties of the product. In the second part international case studies on the global trade of these chemicals and their impact on human health and the environment are presented. This volume is an invaluable source of information for scientists and governmental agencies dealing with the risk assessment of chemicals on a global scale.
Introduction -- Additives in the paper industry -- Additives in the leather industry -- Additives in the electronics -- Additives in the textile industry -- Lubricants and additives: a point of view -- Additives in the plastic industry -- Problems in paper recycling in Vietnam -- Case study on printed matter in Denmark -- Reuse of potential chemical sludge- a hazardous waste in the textile dyeing process -- Risk management of chemicals in the leather sector – a case study from Sweden -- Lubricants recycling: a case study -- Emissions of additives from plastics in the societal material stock - a case study for Sweden -- Recycling WEEE, a case study: Brazil -- Conclusions.
Keywords: Environmental chemistry; Environmental Chemistry